High phosphorus diet mitigates impairments in lipid and glucose metabolism associated with diet-induced obesity in male sprague dawley rats - Bassil, Maya (2016)
Phosphorus (P) nutrition status was found to be inversely related to obesity and metabolic syndrome in observational studies and this is thought to be mediated through an effect of P on liver metabolism (Obeid, 2013). This study thus aims at investigating whether P diet supplementation prevents the metabolic abnormalities associated with diet induced obesity in a controlled animal study. Thirty Sprague-Dawley adult male rats (mean weight = 201±3g) were allocated into 3 equal groups receiving either a balanced diet (control), high fat diet with regular P concentration of 0.3% (HF) or high fat, high P (0.9%) diet (HFHP). Study lasted for 12 weeks, during which body weight and food intake were measured biweekly and intraperitoneal glucose tolerance test (IPGTT) was performed at the beginning (week2) and end (week 11) of the study. Rats were then sacrificed after 10-hour fast, abdominal fat and liver were collected and weighed and serum samples were isolated from venous blood drawn from the inferior vena cava. Serum insulin, cholesterol, triglycerides as well as liver enzymes (ALP and ALT) were measured. High fat diet resulted in a significantly higher body weight gain, food intake and liver weight compared with control, irrespective of P supplementation. HF group had higher abdominal fat (0.44±0.12g) compared to control (0.21±0.06g) but this was not observed in HFHP group (0.29±0.10g). IPGTT results at week11 showed similar baseline glucose among groups but significantly (p=0.05) higher glucose at 2 hours post glucose injection in HF group (127±4.2mg/dl) vs. control (113±5.2 mg/dl) indicating glucose intolerance. P supplementation normalized glycemia at 2 hours in HFHP group (113±5.4 mg/dl). Fasting insulin increased significantly (p=0.008) in HF (2.8±0.4ng/ml) vs. control (1.2±0.4ng/ml) but was not different in HFHP group (2.2±0.5ng/ml). High fat induced obesity significantly (p<0.05) increased serum cholesterol, triglycerides and ALP in HF group (46.1±3.9mg/dl, 38.8±4.4mg/dl and 192.8±55.9U/l, respectively) compared to control (19.8±2.7mg/dl, 26.0.1±3.7mg/dl and 76.6±7.3U/l, respectively) but P supplementation in HFHP prevented this increase. In conclusion, high P diet appears to protect against lipid and glucose abnormalities and liver toxicity associated with diet induced obesity in rats. We suggest that P increases hepatic ATP, which drives the shift from lipid synthesis to glycogen and protein synthesis. Further analysis on the liver tissues will help in identifying the exact mechanisms.